2012
DOI: 10.1590/s1516-35982012000600011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial inoculants and amino acid production by-product on fermentation and chemical composition of sugarcane silages

Abstract: -The objective of this study was to evaluate the chemical composition, fermentation patterns and aerobic stability of sugarcane silages with addition of amino acid production (monosodium glutamate) by-product (APB) and microbial inoculants. Mature sugarcane was chopped and ensiled in laboratory silos (n = 4/treatment) without additives and Mercosil Maís 11C33 ® increased the time elapsed to reach maximum temperature. Monosodium glutamate production by-product does not alter fermentation patterns or aerobic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…VFA analysis was carried out at the Department of Animal Nutrition and Production of the University of São Paulo, Pirassununga (Brazil), according to Rodrigues et al (2012). Briefly, 1 ml of silage juice was mixed with 0.2 ml of formic acid in amber glass bottles.…”
Section: Chemical Composition and Volatile Fatty Acids (Vfa) Concentrmentioning
confidence: 99%
“…VFA analysis was carried out at the Department of Animal Nutrition and Production of the University of São Paulo, Pirassununga (Brazil), according to Rodrigues et al (2012). Briefly, 1 ml of silage juice was mixed with 0.2 ml of formic acid in amber glass bottles.…”
Section: Chemical Composition and Volatile Fatty Acids (Vfa) Concentrmentioning
confidence: 99%
“…The analyses of short-chain fatty acids, ethanol and acid lactic concentration were carried out at the Department of Animal Nutrition and Production, School of Veterinary Medicine and Animal Science − University of São Paulo, Pirassununga, Brazil, according to the methods described by Rodrigues et al (2012). Aliquots of 1 mL of silage juice were mixed with 0.2 mL formic acid in amber glass bottles and stored at −18 • C until analysis.…”
Section: Fermentative Profilementioning
confidence: 99%
“…Rodrigues et al. () have already reported the lack of effect on ethanol concentration in silos with lower acetic acid concentrations. These authors associated this outcome to the magnitude of responses, as observed in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…However, chitosan showed no effect on silage ethanol though there was a lower numerical concentration in silos containing (0.41 g/kg DM) or not (0.05 g/kg DM) microbial inoculant. Rodrigues et al (2012) have already reported the lack of effect on ethanol concentration in silos with lower acetic acid concentrations. These authors associated this outcome to the magnitude of responses, as observed in the present study.…”
Section: Discussionmentioning
confidence: 97%